2016
DOI: 10.1002/bem.21987
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of an electromagnetic hypersensitivity questionnaire for Japanese people

Abstract: The purpose of the present study was to evaluate the validity and reliability of a Japanese version of an electromagnetic hypersensitivity (EHS) questionnaire, originally developed by Eltiti et al. in the United Kingdom. Using this Japanese EHS questionnaire, surveys were conducted on 1306 controls and 127 self‐selected EHS subjects in Japan. Principal component analysis of controls revealed eight principal symptom groups, namely, nervous, skin‐related, head‐related, auditory and vestibular, musculoskeletal, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
(60 reference statements)
1
4
0
Order By: Relevance
“…Further, their symptoms largely overlap with those of other functional syndromes. Rea et al [ 20 ] reported that > 80% of patients with EHS present with MCS, which is consistent with the report by Hojo et al [ 13 ]. Belpomme and Irigaray reported that 30% of the patients with MCS have EHS.…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…Further, their symptoms largely overlap with those of other functional syndromes. Rea et al [ 20 ] reported that > 80% of patients with EHS present with MCS, which is consistent with the report by Hojo et al [ 13 ]. Belpomme and Irigaray reported that 30% of the patients with MCS have EHS.…”
Section: Introductionsupporting
confidence: 86%
“…Hojo et al [ 13 ] developed a Japanese translation of the questionnaire originally published by Eltiti et al [ 11 ], modified it to fit the Japanese lifestyle, and confirmed its reliability and validity. The EHS questionnaire comprises the following sections: Demographics, II-1 Symptoms (57 items, q1–q57), and II-2 EMF-producing objects (nine items, q58–q66) considered to cause the symptoms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the QEESI to define patients with MCS as this tool has been internationally validated [9, 11–13]. Third, we may have overlooked individuals who do not typically access the web; we note that most MCS patients have electromagnetic hypersensitivity [54], which prevents them from using a personal computer. However, some MCS patients have difficulties visiting healthcare facilities owing to potential exposure to chemical substances (such as perfumes and exhaust gases) while on route.…”
Section: Discussionmentioning
confidence: 99%